استخدام القصة في تعليم مهارة الاستماع لطلبة مدرسة المتوسطة الإسلامية باب السلام جوكوراطا: Penggunaan Metode Cerita untuk Mengajarkan Keterampilan Istima’ Siswa MTs Babussalam Jogoroto - Akbar, Dhoyfun (Jiluna Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2024)
Teaching a language begins with teaching listening, then speaking, then reading, then writing. Language teachers must pay attention to these skills, but many teachers do not know the importance of educational methods in the teaching and learning process. There are also those who use methods that are not appropriate to the students' conditions and the requirements of academic subjects. The problem in this research is the lack of good and interesting methods used by Arabic language teachers, so that students feel bored and bored in learning Arabic. The hypothesis of this research is that the results of students in teaching listening skills after using stories are greater than the results of students in teaching listening skills before using stories. This research uses an experimental method, where the researcher chose to design pre and post tests for the experimental and control groups. The population of this study were students in semester VIII-2 of the Babussalam Tambar Jogoroto School, and the sample in this study was 33 students, consisting of 16 students in the experimental group and 17 students in the control group. Among the most important results obtained from this research are the following: (1) The results of students in listening in the experimental group were very good, because they reached an average score of 82, and (2) The results of students in listening in the control group were good, because achieved an average score of 72, and (3) The extent to which the effectiveness of using stories in teaching Arabic to develop listening skills reached a score of T (3.00). compared to the T score in the table at the 5% level (2.04) and the T score in the table at the 1% level (2.75). This shows that the use of stories in teaching Arabic to develop listening skills is effective.